A qualitative assessment of an abstinence-oriented therapeutic community for prisoners with substance use disorders in Kyrgyzstan - Azbel, Lyuba (Harm Reduct J, 2017)
BACKGROUND: Kyrgyzstan, where HIV is concentrated in prisons and driven by injection drug use, provides a prison-based methadone maintenance therapy program as well as abstinence-oriented therapeutic community based on the 12-step model called the “Clean Zone.” We aimed to qualitatively assess how prisoners navigate between these treatment options to understand the persistence of the Clean Zone despite a lack of evidence to support its effectiveness in treating opioid use disorders. METHODS: We conducted an analysis of policy documents and over 60 h of participant observation in February 2016, which included focus groups with a convenience sample of 20 therapeutic community staff members, 110 prisoners across three male and one female prisons, and qualitative interviews with two former Clean Zone participants. Field notes containing verbatim quotes from participants were analyzed through iterative reading and discussion to understand how participants generally perceive the program, barriers to entry and retention, and implications for future treatment within prisons. RESULTS: Our analyses discerned three themes: pride in the mission of the Clean Zone, idealism regarding addiction treatment outcomes against all odds, and the demonization of methadone. CONCLUSION: Despite low enrollment and lack of an evidence base, the therapeutic community is buttressed by the strong support of the prison administration and its clients as an “ordered” alternative to what is seen as chaotic life outside of the Clean Zone. The lack of services for Clean Zone patients after release likely contributes to high rates of relapse to drug use. The Clean Zone would benefit from integration of stabilized methadone patients combined with a post-release program.